1977
DOI: 10.1161/01.cir.56.6.968
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of parasystole and its application to clinical arrhythmias.

Abstract: A ventricular parasystolic focus capable of generating manifest ectopic beats should not be totally insulated from the electrical events that accompany depolarization in the surrounding tissue; the intrinsic cycle length of the ectopic discharge may be modulated by electrotonic influences transmitted across the zone of "protection." To study the nature of the interaction, response patterns were examined in a mathematical model programmed to simulate an ectopic pacemaker protected, but not divorced from ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(72 citation statements)
references
References 20 publications
5
67
0
Order By: Relevance
“…It has been shown that if the impedance of the communication between the ectopic focus and the surrounding ventricle is low, locking of the ectopic pacemaker could be nearly fixed to give the appearance of a reciprocating bigeminy. 18 This is substantiated by Figure 2 in our case, wherein after infusion of amiodarone there is partial suppression of focus A resulting in occasional ectopic beats during sustained monomorphic VT because of focus B. Measurement of B-B intervals shows that there is doubling of the rate from 0.88 s during BVT as seen in Figure 1, compared with 0.44 s in Figure 2 suggesting a parasystole as the mechanism of arrhythmia.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It has been shown that if the impedance of the communication between the ectopic focus and the surrounding ventricle is low, locking of the ectopic pacemaker could be nearly fixed to give the appearance of a reciprocating bigeminy. 18 This is substantiated by Figure 2 in our case, wherein after infusion of amiodarone there is partial suppression of focus A resulting in occasional ectopic beats during sustained monomorphic VT because of focus B. Measurement of B-B intervals shows that there is doubling of the rate from 0.88 s during BVT as seen in Figure 1, compared with 0.44 s in Figure 2 suggesting a parasystole as the mechanism of arrhythmia.…”
Section: Discussionsupporting
confidence: 73%
“…This results in the occurrence of modulated parasystole. 17,18 This means that nonparasystolic beats falling close to the parasystolic beats can cause (1) maximal delay, (2) maximal acceleration, (3) lesser effects, (4) practically no effect, or (5) pacemaker annihilation of the parasystolic focus. 16,19 Nonparasystolic beats falling during the first half of the parasystolic interval induce a prolongation of this interval, those occurring during the second half of the parasystolic cycle length cause an abbreviation of this interval.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of mathematical simulations and experimental studies the investigators showed that the effect of modulation could frequently mask the parasystolic nature of a VEA focus (Moe 1977;Antzelevitch , 1983b. At certain heart rates the timing and coupling intervals of the PVCs appeared to conform to a fixed coupled, reentry-like pattern.…”
Section: Patterns In the Grouding Of Pvcsmentioning
confidence: 99%
“…Inverse solution of some clinical records, however, yielded curves in which the delay phase was of considerably lower amplitude than the acceleration phase.4 6,7 To explain this anomaly, we considered the possibility that the position of the dominant ectopic pacemaker relative to Complete scans of the EP cycles in the experiment depicted in figure 3 are illustrated in figure 4. When the dominant pacemaker was close to the block, the EP firing was delayed by a maximum of 32% and accelerated by 22%/o.…”
Section: Position Of Pacemakermentioning
confidence: 99%
“…1-3 Electrotonic depolarizations that occur early during phase 4 of the spontaneous pacemaker cycle delay the next discharge; those that occur later in the cycle accelerate, or "capture," the pacemaker.3 Thus, the activity of an ectopic focus, "protected" but not insulated by an area of depressed excitability, may be modulated by activity in the surrounding tissue according to a biphasic electrotonic influence or phase-response relationship.…”
mentioning
confidence: 99%